Effect of Equine Erythrocyte Incubation at 49°C on Amphiphilic Substance Efficiency Under Hypertonic Stress Conditions - Shpakova, N. M.; Pisarenko, N. A.; Orlova, N. V. (Problems of Cryobiology and Cryomedicine, 2009)
The effect of amphiphilic compounds (C10, DM, TFP) and heat preliminary treatment of equine erythrocytes (49°C) on cell sensitivity to hypertonic stress (4.0 M NaCl) has been investigated. All amphiphilic compounds were shown as reducing the level of hypertonic hemolysis in equine erythrocytes. Erythrocyte incubation at 49°C, resulting in spectrin denaturation, reduces the level of erythrocyte hypertonic damage at 37°C and increases it at 0°C. A decrease in the efficiency of all studied amphiphilic compounds is observed under the mentioned conditions.